Effects of temperature on mechanical properties of multi-walled carbon nanotubes - Zhang, Y.C.; Chen, X.; Wang, X.
This paper reports the results of an investigation into the effect of environmental temperature on mechanical properties of multiwalled carbon nanotubes (CNTs), by means of a molecular structural mechanics model in which the covalent bonds are treaded as dimensional Euler-Bernoulli beam. Here, van der Waals forces between nearest-neighbor tube layers are firstly simulated by using the nonlinear springs. Based on the ionic plus linear Pauli repulsion model, the sectional stiffness parameters in different environmental temperatures are described as functions of bond stretching, bond bending angle and torsional resistance force constants being dependent of environmental temperature. Results obtained by means of nano-scale finite element simulation reveal that the Young's modulus and Poisson's ratios of multi-walled carbon nanotubes decreases significantly with the increase of environmental temperatures. It is noticed that the Young's modulus of multi-walled Zigzag CNTs is m ore sensitive to environmental temperatures due to the tube chirality. Last, the relationship between Young's modulus of double-walled CNTs and environmental temperature is given by a simple formula.
Keywords: CARBON NANOTUBES; MECHANICAL PROPERTIES; ENVIRONMENTAL TEMPERATURE; MICROMECHANICAL MODELING